ANALISIS FITOKIMIA, SIFAT ANTI BAKTERI DAN ANTIOKSIDAN PROPOLIS Tetragonula sapiens DARI BUTON UTARA - Niken pujirahayu; Zakiah Uslinawaty; Nurhayati Hadjar; Dirvin; Ahmat Gari (Jurusan Kehutanan -FHIL-UHO, 2025)
This study investigates the phytochemical composition, antioxidant, and antibacterial activities of stingless bee, Tetragonula sapiens propolis from four locations in Buton Utara, Southeast Sulawesi, Indonesia. Phytochemical screening confirmed the presence of flavonoids, tannins, and polyphenols in all samples, while alkaloids were absent. Antioxidant activity, measured by DPPH assay, varied significantly among samples, with Lakonea exhibiting the strongest activity (IC₅₀ 42.22 ppm), followed by Linsowu (66.33 ppm), Lemo Ea (85.13 ppm), and Lantagi (113.39 ppm). Antibacterial tests against Escherichia coli, Staphylococcus aureus, and Salmonella typhi revealed distinct inhibitory patterns, with Lakonea showing the broadest spectrum of activity at 30% concentration. Statistical analysis indicated a strong negative correlation (rₛ = -0.80) between IC₅₀ values and total antibacterial inhibition, suggesting that samples with higher antioxidant capacity tend to possess stronger antibacterial effects. The findings highlight the influence of geographical origin and botanical sources on the bioactivity of propolis. This study concludes that stingless bee propolis from Buton Utara, particularly from Lakonea, holds promising potential as a natural source of antioxidants and antibacterial agents, supporting its future application in the development of functional foods, nutraceuticals, and pharmaceuticals.